PENERAPAN MEDIA PERMAINAN KARTU KATA DAN RODA KEBERUNTUNGAN MENINGKATKAN PENGUASAAN KOSAKATA BAHASA MANDARIN SISWA KELAS X - Mulyatik, Mulyatik; Thamrin, Lily; Veronica, Tjen (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The purpose of this study was to understand the use of word card and wheel of fortune game media for teaching Mandarin Vocabulary, it aimed to analyze the advantages and disadvantages of word card and wheel of fortune game media in teaching Mandarin Vocabulary. This research utilized an experimental research method. Data collection methods were in the form of student response questionnaires and written test (Pretest and Posttest). The study"™s result were analyzed using the likert scale method. The comparison between the pretest and posttest result indicates an average improvement of 23.83. Furthermre, the overall comparison between the pretest and posttest demonstrates increases in specific areas: 25.33of improvement in pinyin, 22.67 improvement in meaning, 33 improvement in hanzi, and 31.67 improvement in vocabulary. Therefore, the use of word card and wheel of fortune game media proves to be highly effective in assisting students in mastering Mandarin Vocabulary.